2001
DOI: 10.1097/00001813-200106000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of digitoxin and related cardiac glycosides in human tumor cells

Abstract: The saponin digitonin, the aglycone digitoxigenin and five cardiac glycosides were evaluated for cytotoxicity using primary cultures of tumor cells from patients and a human cell line panel (representing different cytotoxic drug-resistance patterns). Of these seven compounds, proscillaridin A was the most potent (IC(50): 6.4--76 nM), followed by digitoxin, and then ouabain, digoxin, lanatoside C, digitoxigenin and digitonin. Correlation analysis of the log IC(50) values for the cell lines in the panel showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
70
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 23 publications
8
70
0
1
Order By: Relevance
“…In the latter, cardiac glycosides also inhibit testosterone production in vivo (38). Thus, while the cytotoxicity of some cardiac glycosides may correlate with Na ϩ ͞K ϩ -ATPase inhibition (18,21), the present study reveals a unique class of noncardioactive tumor-specific and potent cytotoxins, for which the mechanism of action remains to be elucidated.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In the latter, cardiac glycosides also inhibit testosterone production in vivo (38). Thus, while the cytotoxicity of some cardiac glycosides may correlate with Na ϩ ͞K ϩ -ATPase inhibition (18,21), the present study reveals a unique class of noncardioactive tumor-specific and potent cytotoxins, for which the mechanism of action remains to be elucidated.…”
Section: Resultsmentioning
confidence: 81%
“…The growing body of epidemiological (19,20), in vitro (18), and in vivo (31) evidence supporting the anticancer benefits of cardenolides has prompted the search for noncardioactive analogs that retain anticancer activity. The specific mechanism of cardenolide-induced cytotoxicity remains controversial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, individual reports on oleandrin in TNF-␣-activated HeLa cells have shown that it can block activation of NF-B and activating protein 1 (4,5). Finally, digitoxin itself has been reported to have cytotoxic actions on certain types of human tumor cells in vitro (6,7). Thus, the action of cardiac glycosides on the NF-B pathway may have general implications beyond the specific application to blocking constitutive pathway activation in CF.…”
mentioning
confidence: 99%